Study of Simulation and Experimental Effect of Vaccum Degrees Between Glass Containers and Absorber on Solar Water Heater with Absorber Sinusoidal Type - Royyan Firdaus; Djatmiko Ichsani; Mohamad Hakam; A’rasy Fahruddin (IPTEK Journal of Proceedings Series, 2019)
In this era, the energy crisis is the spotlight, as many of us rely heavily on non-renewable energy such as fuel oil and natural gas, so that if the fuel source runs out, then all life processes will also stop. Not only that, the pollution caused by the use of fuel oil is very bad for the environment. Therefore, there is need for savings in all aspects of life that require energy. One of them is solar energy. In this research we are researching how to analyze and make solar water heater experiments effective and efficient so that can be widely used by many people. Solar water heater is very varied in terms of methods used to take the sun's heat. It all depends on the design and analysis made. In this case the wide absorption of solar thermal energy absorbed by the absorber is also very important, for that we use sinusoidal-shaped absorber plate. Furthermore, through the journals that ever existed, the researchers took 2 important aspects that need to be in the study that is with the variation of vacuum and discharge rates with the thickness of the sinusoidal (δ) 2 mm absorber plate. For the vacuum level will be varied 0 mm.Hg, -20 mm.Hg, -40 mm.Hg, -60 mm.Hg, -80 mm.Hg, -100 mm.Hg, -120 mm.Hg and by varying the fluid flow of work by adjusting the valve opening, that is from 18 L/hour to 22 L/hour with increase of 2 L/hour. By varying the level of vacuum between the absorber plate and the cover glass, it is expected to minimize the loss coefficient, increase the temperature of the absorber, and the temperature of the cover glass down. So it can improve collector efficiency 63.29%. and usefull Heat 760.39 Watt/m2, when the solar collector is set at a discharge of 22 L/hour, vacuum level -120 mmHg